Maximizing Employee Performance: The Impact of Motivation and Work Environment in a Bandung-Based Convection Business - Oktaviani, Nurul; Danasasmita, Windi Matsuko (Journal of Economics, Management, and Entrepreneurship, 2025)
This study aims to investigate how employee performance is impacted by work environment and motivation. In this study, a descriptive and verifiable strategy was employed. Statements (questionnaires) sent to employees of one of the Bandung convective enterprises served as the study's data source. There are thirty-five participants in the study. The research utilizes both descriptive and verificative statistical methodologies. They helped with the SPSS (Statistical et al.) version 26 application by applying Correlation Data Analysis, Path Analysis, and Determination Coefficient Analysis. Motivation, Work Environment, and Employee Performance in one of the Bandung convection enterprises was determined to be related based on the entire data analysis. Thus, the work environment and motivation have an impact on employee performance. Other elements that may impact employee performance should be covered in this study. Furthermore, in comparison to the work environment, motivation has less of an effect. Therefore, the business ought to prioritize the work environment while simultaneously maximizing employee motivation at one of Bandung's convective businesses.